Development of a Nested PCR for Environmental Detection of the Pathogenic free-living Amoeba Balamuthia mandrillaris - Ahmad, A.F.; Andrew, P.W.; Kilvington, S. (2011)
A DNA extraction and nested PCR method for detecting the pathogenic amoeba Balamuthia mandrillaris from the environment was developed. Sixteen of 17 Californian soil samples were positive compared with 0/44 from the United Kingdom. This approach will enable a greater understanding of B. mandrillaris ecology, geographic distribution, and public health risk.